Spontaneous Adrenal Hematoma in a Pregnant Woman; a Case Report - Ghasemi, Mahshid; Beigi, Ali Akbar; Behnaz, Faranak; Fathi, Farhad; Memary, Elham (Archives of Academic Emergency Medicine, 2017)
Spontaneous adrenal hematoma is a very rare condition and its prevalence has been reported to be about 1% in previous studies. Although various causes have been proposed to explain its incidence in existing case reports, the etiology and pathology of this condition is still not known. The present study presents a case of spontaneous adrenal hematoma in a pregnant 31 year old woman without history of trauma or other probable risk factors of hemorrhage, presenting to the emergency department with chief complaint of pain in the right flank. Diagnostic measures, imaging and laparotomy, confirmed the diagnosis of spontaneous adrenal hematoma for her.